Efektivitas Strategi Pemasaran dalam Penerapan Metode Grade Terhadap Peningkatan Kesejahteraan Petani Buah Nanas - Kiki Samsudin; Agus Sumarna; Wawan Kurniawan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research is motivated by Applying the grade method to marketing strategies that can prevent occurrences that can give rise to the practice of gharar, which in Islamic religious teachings prohibits buying and selling that is uncertain, unclear and contains gambling. The aim of this research is to find out Effectiveness of Marketing Strategy in Applying the Grade Method to Increasing the Welfare of Pineapple Farmers. This research uses a qualitative approach. The results of this research show the impact of applying the grade method in pineapple marketing strategies on farmer welfare. With this method pineapple fruit can be classified based on its quality, so farmers can get better prices for high grade products. In addition, by improving product quality, marketing can reach a wider market, which can ultimately increase farmers' income and their overall welfare. Even though this year there has been a decline in income, this is also due to external factors. The impact of pineapple farming on local communities and the economy is very significant, creating job opportunities, increasing people's income, and encouraging local economic growth.